Measurement of Practices-Knowledge-Attitudes of the Nursing Process: Systematic Review - Camargo-Figuera, Fabio Alberto; Ortega-Barco, María Alejandra; Rojas-Plata, María Camila; Marín-Rodríguez , Daniela; Alarcón-Meléndez, Lizeth Johana; Villamizar-Carvajal, Beatriz (Investigación y Educación en Enfermería, 2021)
Objective. To analyze the literature available on the psychometric properties of the instruments to measure knowledge, attitudes, and practices of the nursing care process. Methods. This was a narrative-type review conducted by following the recommendations of the PRISMA declaration. The search strategy was executed in two stages; through the search in databases by two reviewers and – thereafter – three reviewers identified independently the studies and evaluated the methodological quality of the measurement instruments by using the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) property checklist boxes. Results. Of 71 studies identified for the full-text review, only seven complied with the inclusion criteria that represent four instruments (Q-DIO, D-CATCH, NP-CDSS, PNP). It was found that the instruments continue in their validation and appropriation processes to reality in health services. Conclusion. In spite of the evident evolution of the instruments to evaluate the implementation of the nursing care process, the need is still valid for an instrument that measures aspects of knowledge, attitudes, and practices in every stage of the process.